Pengaruh Penerapan Sistem E-Filing Dan Relawan Pajak Terhadap Kepatuhan Wajib Pajak Orang Pribadi - Listiani Listiani; Andri indrawan; Hendra Tanjung (AKUNTANSI 45, 2023)
This study aims to analyze the effect of implementing the E-Filing system and tax volunteers on individual taxpayer compliance at KPP Pratama Sukabumi using a quantitative method approach. The data collection method in this study is using primary data. The data analysis technique used is multiple linear regression, based on the results of multiple linear regression, the regression equation Y = 11.106 + 0.459X1 + 0.266X2 is obtained. The results of research and partial hypothesis testing show that the Application of the E-Filing System has a significant effect on individual taxpayer compliance, a significance value of 0.001> 0.05 and a calculated t value of 3.403> t table 1.985, The role of Tax Volunteers has a significant effect on individual taxpayer compliance, a significance value of 0. 000 < 0.05 and the value of f count 3.699> f table 1.985, Simultaneously the E-Filing system and the role of tax volunteers have a significant joint effect on individual taxpayer compliance, the significance value is 0.000 < 0.05 and the value of f count 21.768> f table 3.09.